Human growth factor-mediated signalling through lipid rafts regulates stem cell proliferation, development and survival of Schistosoma mansoni - Shradha Maharjan; Ruth S. Kirk; Scott P. Lawton; Anthony J. Walker (Open Biology, 2024)
Although the mechanisms by which schistosomes grow and develop in humans are poorly defined, their unique outer tegument layer, which interfaces with host blood, is considered vital to homeostasis of the parasite. Here, we investigated the importance of tegument lipid rafts to the biology of Schistosoma mansoni in the context of host–parasite interactions. We demonstrate the temporal clustering of lipid rafts in response to human epidermal growth factor (EGF) during early somule development, concomitant with the localization of anteriorly orientated EGF receptors (EGFRs) and insulin receptors, mapped using fluorescent EGF/insulin ligand. Methyl-β-cyclodextrin (MβCD)-mediated depletion of cholesterol from lipid rafts abrogated the EGFR/IR binding at the parasite surface and led to modulation of protein kinase C, extracellular signal-regulated kinase, p38 mitogen-activated protein kinase and Akt signalling pathways within the parasite. Furthermore, MβCD-mediated lipid raft disruption, and blockade of EGFRs using canertinib, profoundly reduced somule motility and survival, and attenuated stem cell proliferation and somule growth and development particularly to the fast-growing liver stage. These findings provide a novel paradigm for schistosome development and vitality in the host, driven through host–parasite interactions at the tegument, that might be exploitable for developing innovative therapeutic approaches to combat human schistosomiasis.